Assessment frequency in introductory computer programming disciplines - Brito, Miguel A. (2014)
Introductory computer programming disciplines commonly show a significant failure rate. Although several reasons have been advanced for this state of affairs, we argue that for a beginner student it is hard to understand the difference between know-about disciplines and know-how-to-do-it disciplines, such as computer programming. This leads to failure because when students understand they are not able to solve a programming problem it is usually too late to catch all the time meanwhile lost. In order to make students critically analyse their progress, instructors have to provide them with realistic indicators of their performance. To achieve this awareness and to trigger corrective actions in a timely manner there is a need to increase assessment frequency. This paper discusses how this can be done, analyses benefits of the proposed approach and presents data on the effects of changes in assessment frequency for a university first year course in fundamentals of computer programming.